DIVIDE-AND-CONQUER: A SYSTEMATIC APPROACH FOR SUBCONTRACTOR SELECTION IN DEFENSE INDUSTRY PROJECTS - Şehitoğlu, Anıl; Chouseinoglou, Oumout (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
The defense industry projects’ sizes are generally large and may be broken down into subparts of different granularity levels, where each subpart may be assigned to a different subcontractor. On the other hand, the problem of subcontractor selection to each subpart is a complex decision-making problem that requires evaluating several criteria and the characteristics of each subpart. This study aims to model the problem of subcontractor selection in a defense industry project decomposed to multiple subprojects by combining the Analytic Hierarchy Process (AHP) and Integer Linear Programming (ILP). A project carried out at a defense industry company in Turkey has been used as a case study. An extensive set of criteria specific to the defense industry have been identified, and AHP has been applied to the relevant criteria and alternative subcontractors for each subpart. Finally, ILP has been used to include a set of constraints regarding the project specifications.